Expression of inflammatory cytokines and MMPs on replanted teeth at different extra‐alveolar time: an ex vivo and in vivo study. Issue 4 (7th November 2015) - Ahn, Hyo Jung; Nam, Ok Hyung; Lee, Hyo‐Seol; Kim, Eun‐Cheol; Cohenca, Nestor; Choi, Sung Chul
Abstract : Background: Immediately after the avulsed tooth is replanted, a complex inflammatory response ensues. As part of the periodontium healing process, the extracellular matrix macromolecules are essential to create the cellular environment required during healing and morphogenesis. Aim: This study was designed to evaluate the correlation between different extra‐alveolar dry times and inflammatory cytokines and matrix metalloproteinases (MMPs) as part of the periodontal ligament (PDL) gene expression. Design: The first phase of the study aimed testing human PDL cells ex vivo . Extracted teeth were dried for 15 and 30 min. The PDL cells were extracted and analyzed by qRT‐PCR. The second phase was performed in vivo, and 36 Sprague Dawley rat first maxillary molars were extracted and replanted after 15, 30, and 60 min extra‐alveolar time. We tested the levels of inflammatory cytokines and MMPS in periodontal tissue at 3, 7, and 28 days after tooth replantation. The replanted area was dissected, grounded, and analyzed by RT‐PCR. Results: Expressions of IL‐1 β, IL‐6, TNF‐ α, and MMP‐3 and MMP‐9 were significantly higher in the replanted teeth. Extended dry time had a direct correlation with induction of pro‐inflammatory cytokine and MMPs in PDL cells. Conclusion: Our study showed that pro‐inflammatory cytokines were more significantly expressed in the tissues surrounding the replanted teeth. Future research must be undertaken to additionally confirm the release of these cytokines and be focused on the inhibition of these cytokines to reduce inflammation of replanted teeth.